Beach handball goalkeeper defense times (Research, Society and Development, 2022)
In the beach handball, the goalkeeper is one of the most important figures in the team, being considered the last defender and the first attacker, with a privileged view of the entire game. Therefore, it is essential that your training is based on sensory-motor stimuli that simulate the situations experienced in the day to day of the modality. In Brazil, currently, few efforts have been dedicated to the training of the Beach Handball goalkeeper. The literature still has few resources for this purpose. Thus, the objective of this study is to develop a guideline for the training of the Beach Handball goalkeeper, taking into account the necessary stimuli according to the analysis of each stage of defense. The proposal has as a differential the addition of a fourth time that includes the characteristics of Beach Handball. With this, it is expected that the coach can adapt this training method to each goalkeeper profile he has in his team and they can achieve better performance over time.